Leveraging Expertise for Digitalizing Indonesian Public Sector Performance Audits - Mahsun, Mohamad; Popoola, Oluwatoyin Muse Johnson (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2025)
Global digital transformation is reshaping audit practices through technologies such as data analytics, artificial intelligence, and automation that enhance accuracy, efficiency, and scope. This study explores Indonesian auditors' perspectives and experiences regarding audit digitalization, particularly in the context of public sector performance audits. This qualitative research employs semi-structured interviews with 8 auditors from audit firms, analyzed using Braun and Clarke's thematic analysis approach. The study examines auditors' understanding of perceived benefits, encountered obstacles, required new skills, and necessary support for integrating digital technologies into audit activities. Findings reveal that audit digitalization offers significant benefits in efficiency, accuracy, and transparency, yet implementation faces challenges including limited human resources, poor data quality, and high costs. Auditors require both technical and non-technical skills, along with training and infrastructure support from audit firms. For the public sector, digitalization holds substantial potential for strengthening accountability and enabling data-driven policymaking. However, challenges such as bureaucratic barriers, inadequate data integration, and limited information systems infrastructure must be addressed. This study provides valuable insights and practical recommendations to support the digitalization of Indonesian public sector performance audits, ultimately enhancing the effectiveness and efficiency of public resource utilization.